The Teacher who Teaches Mathematics and their Education: an experience in Portugal - Maria de Lurdes Serrazina (Universidade Federal do Rio Grande do Sul, 2014)
This paper discusses the characteristics of continuing education for polyvalent teachers in mathematics, which may lead to changes in their attitude towards mathematics and their classroom practices. It approaches the Continuous Education Program in Mathematics (PFCM), developed in Portugal. It discusses the knowledge of the teacher to teach mathematics, the types of knowledge required for a proficient teaching, and relates them to the development of a confidence attitude in the teacher as the one who teaches mathematics. It presents the case of a teacher, trainee of PFCM for two years, highlighting the contribution of the program for the development of her knowledge and position as a teacher who teaches mathematics.